2013
DOI: 10.4102/sajhivmed.v14i4.51
|View full text |Cite
|
Sign up to set email alerts
|

Perceived adherence barriers among patients failing second-line antiretroviral therapy in Khayelitsha, South Africa

Abstract: Background. The recent scale-up of antiretroviral therapy (ART) coverage in resource-limited settings has greatly improved access to treatment. However, increasing numbers of patients are failing first- and second-line ART.Objective. To examine factors affecting adherence to second-line ART from the perspective of clinic staff and patients, assessing both individual and structural perceived barriers.Methods. Research was conducted at a large primary care tuberculosis (TB)/HIV clinic in Khayelitsha, a peri-urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thirty-three out of 39 studies reported that perceived adverse ARV reactions decreased adherence [12, 15–46], whilst six studies [4752] described no apparent relationship. Nineteen studies [12, 1527, 29, 32, 36, 44, 47] were conducted in high-income countries, eight [30, 31, 33, 34, 41, 42, 46, 49] in middle-income countries, and twelve [28, 35, 3740, 43, 45, 48, 5052] in low-income countries. (Countries—see Tables 1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three out of 39 studies reported that perceived adverse ARV reactions decreased adherence [12, 15–46], whilst six studies [4752] described no apparent relationship. Nineteen studies [12, 1527, 29, 32, 36, 44, 47] were conducted in high-income countries, eight [30, 31, 33, 34, 41, 42, 46, 49] in middle-income countries, and twelve [28, 35, 3740, 43, 45, 48, 5052] in low-income countries. (Countries—see Tables 1, 2).…”
Section: Resultsmentioning
confidence: 99%
“…Facing extreme poverty and hunger on a daily basis while trying to cope with the complex health issues associated with HIV could understandably increase stress levels. Studies indicate that when people are stressed they are more likely to drink, and consequently, forget to take their medication [ 45 , 46 ]. Our study revealed forgetfulness to be a significant barrier to ART adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the participants suggested that education on the benefits of taking ART could improve adherence, whilst a few participants also suggested the implementation of injectable ART. Various studies have recommended similar strategies, 49,50,51 with the effectiveness of some of these strategies being previously reported for first-line regimens. 51,52…”
Section: Discussionmentioning
confidence: 99%